Figurative Language in Album “Purpose” by Justin Bieber - Muhammad Syahril Sidiq; Indri Kustantinah; Ririn Ambarini (Lingua Franca, 2023)
This study aims to (1) find out the figurative language in the album "Purpose" by Justin Bieber, (2) find out the meaning of the lyrics using figurative language in the album "Purpose" by Justin Bieber, (3) find out the most dominant type of figurative language in the album "Purpose" Purpose" by Justin Bieber. This research is qualitative with a library research model. As literary research, the research data is figurative language in the album "Purpose" by Justin Bieber. Data collection techniques using documentation. At the same time, data analysis is done by analyzing song lyrics, interpretation, classification, and conclusion. The study results indicate several types of figurative language in the album "Purpose" by Justin Bieber, namely metaphors, similes, hyperboles, metonymy, apostrophes, and symbols. This study concludes that simile is the most dominant type of figurative language in the album "Purpose" by Justin Bieber.